2018
DOI: 10.1371/journal.pone.0196421
|View full text |Cite
|
Sign up to set email alerts
|

Personal, social, and environmental factors associated with lifejacket wear in adults and children: A systematic literature review

Abstract: ObjectiveDrowning claims 7% of the global burden of injury-related deaths. Lifejackets are routinely recommended as a drowning prevention strategy; however, a review of related factors regarding lifejacket wear has not previously been investigated.MethodsThis systematic review examined literature published from inception to December 2016 in English and German languages. The personal, social, and environmental factors associated with lifejacket wear among adults and children were investigated, a quantitative ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 48 publications
2
29
3
Order By: Relevance
“…Further data from our study suggest that available life jackets are considered unaffordable (ranging from ~US$15 to 150); the cheapest (non-ISO-conforming buoyancy vests) are seen by fishers as uncomfortable and ineffective (data not shown). A recent systematic review reported comfort, accessibility and ownership, and confidence in life jackets as key factors related to life jacket use 23. Male gender and adult age were associated with non-use of life jackets.…”
Section: Discussionmentioning
confidence: 99%
“…Further data from our study suggest that available life jackets are considered unaffordable (ranging from ~US$15 to 150); the cheapest (non-ISO-conforming buoyancy vests) are seen by fishers as uncomfortable and ineffective (data not shown). A recent systematic review reported comfort, accessibility and ownership, and confidence in life jackets as key factors related to life jacket use 23. Male gender and adult age were associated with non-use of life jackets.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, between 2002/03 and 2011/12, an average of 289 people died in Australia due to unintentional drowning [11]. Common fatal drowning scenarios in Australia include young children drowning unsupervised in bathtubs [17] and swimming pools [15] and adult males drowning in natural waterways such as beaches, oceans and in rivers [16] due to alcohol, pre-existing medical conditions [18] and not wearing a lifejacket [19]. Rivers are the leading location for drowning in Australia [11] with leading activities being undertaken prior to drowning including accidental falls into water (21.3%), non-aquatic transport incidents (commonly driving a motor vehicle into floodwaters) (18.2%) and swimming (16.2%).…”
Section: Introductionmentioning
confidence: 99%
“…A barrier to use in LMICs, however, is access to low-cost lifejackets 4. Despite 57% of respondents to the Delphi process stating that the river drowning strategy of ‘ Wear a lifejacket ’ would be effective in both HICs and LMICs, there is a dearth of research from rivers and LMICs on the issue of lifejackets 35. Lifejackets must be seen as an active prevention strategy (to be worn whenever boating), rather than a reactive one (putting a lifejacket on once the boat has capsized) 36.…”
Section: Discussionmentioning
confidence: 99%
“…Lifejackets must be seen as an active prevention strategy (to be worn whenever boating), rather than a reactive one (putting a lifejacket on once the boat has capsized) 36. Although beyond the scope of this Delphi, the authors note that any river drowning prevention strategy focused on lifejackets must address the personal, social and environmental factors underpinning lifejacket wear behaviour,35 as well as suitability and availability of lifejackets in the particular country where they are proposed to be used.…”
Section: Discussionmentioning
confidence: 99%